NON-TARIFF DIMENSION OF NEOPROTECTIONISM IN WORLD TRADE IN AGRI-FOOD PRODUCTS - Karolina Pawlak (Annals of the Polish Association of Agricultural and Agribusiness Economists, 2022)
The aim of this paper was to determine the scope of non-tariff measures used in the world agri-food trade in 2020. This study used data of the United Nations Conference on Trade and Development (UNCTAD) and the Global Trade Alert data. Applying the methodology developed by the UNCTAD and the World Trade Organization (WTO) three indexes were established to describe the use of non-tariff measures (NTMs) to trade, i.e., the Frequency Index, the Coverage Ratio and the Prevalence Ratio. The number of trade preferences and trade restrictions used by the largest exporters and importers of agri-food products was also measured. The analysis showed that the scope of use of non-tariff protection measures in world trade in agri-food products is much greater compared to other branches of the economy. In countries implementing a highly protectionist trade policy, such as Brazil, China, India, Indonesia, Canada, the USA and Vietnam, non-tariff instruments were used in relation to all tariff lines and the entire value of import. To the greatest extent, non-tariff protection measures were adopted in the trade of non-processed plant origin products, including cereals, oilseeds and oleaginous fruit, fruit and vegetables, as well as dairy products. Countries most commonly implementing trade restrictions against their partners and, at the same time, at greatest risk of retaliatory actions on their part included EU countries, the USA and China.